Cardiac Standstill With Intracardiac Clot Formation - Jeffrey Tadashi Sakamoto; Ian Storch; Laleh Gharahbaghian (Clinical Practice and Cases in Emergency Medicine, 2019)
This case describes and depicts cardiac standstill with thrombosed blood within the chambers of the heart. This was likely due to stasis of blood from a prolonged no-flow state. After viewing this ultrasound finding, the decision was made to halt resuscitative efforts in this case of a patient in cardiac arrest.